Penerapan Peraturan Daerah Kota Tasikmalaya Nomor 12 Tahun 2009 Dalam Membangun Kehidupan Masyarakat Berlandaskan Ajaran Islam - Safitri, Annida; R, Rudiana (Media Hukum Indonesia (MHI), 2025)
The Regional Regulation (Perda) of Tasikmalaya City Number 12 of 2009 concerning the Development of Community Life Values Based on Islamic Teachings and Social Norms is a strategic effort to create a harmonious, religious, and Islamic value-based social order. This regulation stems from Tasikmalaya's identity as a "santri city," where the majority of its population adheres to Islam. This study employs a qualitative descriptive method based on library research to analyze the policy implementation through the variables of policy content and policy environment. The findings indicate that while this regulation strengthens religious values, challenges such as social diversity and inclusivity require attention. The role of the government, society, and supporting actors is crucial to ensuring the sustainability of its implementation.